Implementasi Program Pengabdian Masyarakat Dalam Pencegahan Penyakit Tidak Menular Melalui Pemeriksaan Tekanan Darah dan Asam Urat - Riska Fajar Fatony; Annisa’ Arifatul Hikmah; Elsa Tursina; Trisakti Halimah Delimasari; Muhammad Yusuf (Jaanur Elbarik Indonesia, 2026)
This community service program aims to raise public awareness of hyperuricemia risk factors through health screening, education, and community empowerment in adopting healthy lifestyle behaviors. The activities were conducted in Ngawi Regency, East Java, using an approach that included initial coordination, uric acid level testing, blood pressure and Body Mass Index (BMI) measurements, health education, and an evaluation of participants’ understanding. A total of 21 participants took part in the health screening. The results showed that 71.43% of participants were in the ≤55 age group, and the majority were employed (57.14%). Based on nutritional status, 42.86% of participants were obese and 28.57% were overweight. Blood pressure measurements showed that 61.90% of participants had high blood pressure, while 57.14% had high uric acid levels. Participants with high blood pressure had a higher average age compared to those with normal blood pressure. The educational sessions demonstrated an increase in participants’ understanding of risk factors for hyperuricemia, the importance of weight management, dietary adjustments, physical activity, and regular health check-ups.